Multiple Notch signaling events control Drosophila CNS midline neurogenesis, gliogenesis and neuronal identity. - Wheeler, S.R.; Stagg, S.B.; Crews, S.T. (Development, 2008)
The study of how transcriptional control and cell signaling influence neurons and glia to acquire their differentiated properties is fundamental to understanding CNS development and function. The Drosophila CNS midline cells are an excellent system for studying these issues because they consist of a small population of diverse cells with well-defined gene expression profiles. In this paper, the origins and differentiation of midline neurons and glia were analyzed. Midline precursor (MP) cells each divide once giving rise to two neurons; here, we use a combination of single-cell gene expression mapping and time-lapse imaging to identify individual MPs, their locations, movements and stereotyped patterns of division. The role of Notch signaling was investigated by analyzing 37 midline-expressed genes in Notch pathway mutant and misexpression embryos. Notch signaling had opposing functions: it inhibited neurogenesis in MP1,3,4 and promoted neurogenesis in MP5,6. Notch signaling also promoted midline glial and median neuroblast cell fate. This latter result suggests that the median neuroblast resembles brain neuroblasts that require Notch signaling, rather than nerve cord neuroblasts, the formation of which is inhibited by Notch signaling. Asymmetric MP daughter cell fates also depend on Notch signaling. One member of each pair of MP3-6 daughter cells was responsive to Notch signaling. By contrast, the other daughter cell asymmetrically acquired Numb, which inhibited Notch signaling, leading to a different fate choice. In summary, this paper describes the formation and division of MPs and multiple roles for Notch signaling in midline cell development, providing a foundation for comprehensive molecular analyses.